Health promoting school: a comprehensive situation analysis - Mandal, Rajdip (International Journal of Research in Medical Sciences, 2025)
Background: Situation analysis regarding health in an organisation or community is the systematic process of collecting, analysing, and interpreting data about health issues within a specific population or community. Given this context, the present study conducted a practical comprehensive school-related health situation analysis by utilising nine (9) distinct components (physical components to school health policies) regarding the HPS of a selected government higher secondary high school in Sundarban district, West Bengal, India. Methods: A school-based cross-sectional study was conducted from October 2024 to November 2024. A close-ended predesigned, structured questionnaire was used, and quantitative research methods were applied. Results: The analysis of 1,417 responses about the nine health promotion components reveals crucial insights into school health support. Notably, 424 (30%) respondents definitively “no” stated the components were absent, while 157 (11%) found them "not adequate." Additionally, 447 (31.5%) provided "no remark," indicating uncertainty or disengagement. Conversely, 389 (27.5%) affirmed the components were satisfactory with a "yes". Conclusions: This mixed feedback highlights the need for targeted interventions to improve the perceived adequacy of school health services and support systems. It is clear that while some aspects may be functioning well, there is a significant opportunity for enhancement across all nine components.